TREATMENT OF WASTEWATER FROM THERMAL POWER PLANTS AND THE EVALUATION OF A PHYSICO-ELECTROCHEMICAL PURIFICATION METHOD - Тичковський, Сергій; Челядин, Любомир (SWorldJournal, 2025)
The characteristics of wastewater, as well as the technologies and equipment used for its treatment at thermal power plants (TPPs), are presented. The permissible concentrations of harmful substances typical for the energy sector before discharge into wat